Optical laminated body and display device

The optical laminate addresses the challenge of improving display performance in multiple-panel display devices by incorporating a polarizing film with iodine and nitroxyl compounds, and high-haze adhesive layers, resulting in enhanced contrast and reduced optical issues.

JP2025065977APending Publication Date: 2025-04-22NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023175528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Display devices using multiple display panels face challenges in improving image contrast and performance, particularly in effectively utilizing optical members like polarizing and phase difference members.

Method used

The optical laminate includes a polarizing plate with a polarizing film made of polyvinyl alcohol containing iodine and a compound with a nitroxyl radical or nitroxide group, along with adhesive layers that have a high haze, enhancing light diffusion and image display performance.

Benefits of technology

The optical laminate improves the display performance of multiple-panel display devices by enhancing contrast and reducing issues like moiré and polyeneization, while maintaining optical properties and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065977000001_ABST
    Figure 2025065977000001_ABST
Patent Text Reader

Abstract

To provide an optical laminated body that is suitable for a display device using a plurality of display panels.SOLUTION: An optical laminated body 60 comprises: a polarizer 30 that includes a polarization film 10 having a first principal plane 10a and a second principal plane 10b that face each other; a first adhesive layer 41 that is arranged on a first principal plane 10a side of the polarization film 10; and a second adhesive layer 42 that is arranged on a second principal plane 10b side of the polarization film 10. At least one of the first adhesive layer 41 and second adhesive layer 42 has a haze equal to or more than 66%, and the polarization film 10 composed of a polyvinyl alcohol-based film including iodine includes a compound having a nitroxy radical, or a nitroxide group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical laminate and a display device. [Background technology]

[0002] Depending on the application of a display device, such as a liquid crystal display device, there may be a demand for further improvement in the contrast of a displayed image.

[0003] For example, a technique for improving the contrast of a liquid crystal display device has been proposed in which two display panels are overlapped and an image is displayed on each of the display panels (see, for example, Patent Document 1). Specifically, it has been proposed to improve contrast by displaying a color image on the front display panel (observer side) of two display panels arranged in front and behind, and displaying a black and white image on the rear display panel (backlight side). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-310161 A Summary of the Invention [Problem to be solved by the invention]

[0005] In display devices, optical members such as polarizing members and retardation members are generally used to realize image display and improve the performance of the image display. However, display devices using multiple display panels may encounter problems that do not occur in display devices using a single display panel.

[0006] In view of the above, a main object of the present invention is to provide an optical laminate suitable for a display device using a plurality of display panels. [Means for solving the problem]

[0007] 1. An optical laminate according to an embodiment of the present invention comprises a polarizing plate including a polarizing film having first and second main surfaces facing each other, a first pressure-sensitive adhesive layer arranged on the first main surface side of the polarizing film, and a second pressure-sensitive adhesive layer arranged on the second main surface side of the polarizing film, wherein at least one of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer has a haze of 66% or more, and the polarizing film is composed of a polyvinyl alcohol-based film containing iodine and contains a compound having a nitroxy radical or a nitroxide group. 2. In the optical laminate described in 1 above, the second pressure-sensitive adhesive layer may have a haze of 66% or more. 3. The optical laminate according to 2 above may further include a third pressure-sensitive adhesive layer disposed on the second main surface side of the polarizing film. 4. The optical laminate according to 2 or 3 above may further include a support disposed on the second main surface side of the polarizing film. 5. In the optical laminate according to any one of the above items 1 to 4, the content of the compound having a nitroxy radical or a nitroxide group in the polarizing film may be 20% by weight or less. 6. In the optical laminate according to any one of 1 to 5 above, the iodine content of the polarizing film may be 1% by weight or more and 15% by weight or less. 7. In the optical laminate described in any one of 1 to 6 above, the first pressure-sensitive adhesive layer may be formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer and a crosslinking agent, the crosslinking agent may contain an isocyanate-based crosslinking agent, and the content of the isocyanate-based crosslinking agent may be less than 1 part by weight per 100 parts by weight of the (meth)acrylic polymer. 8. In the optical layered body described in 7 above, the isocyanate-based crosslinking agent may be a non-aromatic ring type. 9. A display device according to an embodiment of the present invention is a display device in which a plurality of display panels, each including a liquid crystal cell, are arranged in a stacked manner and images are displayed on each of the display panels, and the display device comprises a first display panel, a second display panel arranged closer to a viewer than the first display panel, and an optical laminate described in any one of 1 to 8 above arranged between the first display panel and the second display panel, and the first adhesive layer of the optical laminate is bonded to the first display panel. Effect of the Invention

[0008] According to the optical laminate according to the embodiment of the present invention, the characteristics of a display device using a plurality of display panels can be improved. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view showing a general configuration of an optical laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a general configuration of an optical laminate according to a second embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view illustrating an outline of a liquid crystal display device according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.

[0011] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0012] [Optical laminate] FIG. 1 is a schematic cross-sectional view showing a schematic configuration of an optical laminate according to a first embodiment of the present invention. The optical laminate 60 includes a polarizing plate 30. The polarizing plate 30 includes a polarizing film 10 having a first main surface 10a and a second main surface 10b facing each other, a first protective layer 21 arranged on the first main surface 10a side of the polarizing film 10, and a second protective layer 22 arranged on the second main surface 10b side of the polarizing film 10. The optical laminate 60 also includes a first pressure-sensitive adhesive layer 41 arranged on the first main surface 10a side of the polarizing film 10, and a second pressure-sensitive adhesive layer 42 arranged on the second main surface 10b side of the polarizing film 10. The first protective layer 21 may also function as a retardation layer. In this case, the first protective layer (retardation layer) 21 may have any appropriate optical characteristics (for example, refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient, etc.).

[0013] Although not shown, the polarizing plate 30 may have an adhesive layer for bonding a protective layer to the polarizing film 10. In the polarizing plate 30 shown in FIG. 1, an adhesive layer may be provided between the polarizing film 10 and the first protective layer 21, and an adhesive layer may be provided between the polarizing film 10 and the second protective layer 22.

[0014] The optical laminate 60 includes a support 50 disposed on the second main surface 10b side of the polarizing film 10. A second pressure-sensitive adhesive layer 42 is disposed between the polarizing plate 30 and the support 50. Specifically, the support 50 is attached to the polarizing plate 30 via the second pressure-sensitive adhesive layer 42.

[0015] The optical laminate 60 includes a third pressure-sensitive adhesive layer 43 disposed on the second main surface 10b side of the polarizing film 10. In the illustrated example, the third pressure-sensitive adhesive layer 43 is provided on the surface of the support 50. The first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43 enable the optical laminate 60 to be attached to another member. For example, the first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43 enable the optical laminate 60 to be attached to a display panel.

[0016] In practice, release liners (not shown) are attached to the surfaces of the first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43, respectively, and the first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43 can be protected by the release liners. The release liners are temporarily attached to the first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43, for example, until the optical laminate 60 is used. Specifically, the release liners are temporarily attached to the first pressure-sensitive adhesive layer 41 and the third pressure-sensitive adhesive layer 43 until the optical laminate 60 is attached to a display panel. A plastic film having a surface coated with a release agent is typically used as the release liner.

[0017] 2 is a schematic cross-sectional view showing an outline of the configuration of an optical laminate according to a second embodiment of the present invention. In the second embodiment, the optical laminate 61 differs from the first embodiment in that a support 50 and a third pressure-sensitive adhesive layer 43 are not provided. In the second embodiment, the optical laminate 61 can be attached to another member by a second pressure-sensitive adhesive layer 42 instead of the third pressure-sensitive adhesive layer 43. In practice, a release liner (not shown) is attached to the surface of the second pressure-sensitive adhesive layer 42, and the second pressure-sensitive adhesive layer 42 can be protected by the release liner.

[0018] At least one of the first pressure-sensitive adhesive layer 41 and the second pressure-sensitive adhesive layer 42 has a haze of, for example, 66% or more and 99% or less, and preferably 70% or more. A pressure-sensitive adhesive layer having such a haze can function as, for example, a light diffusion layer.

[0019] The adhesive layer that can satisfy the above haze typically contains fine particles. Examples of the fine particles contained in the adhesive layer include inorganic fine particles that may have electrical conductivity, such as silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide, crosslinked or uncrosslinked organic fine particles made of various polymers such as polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate, and silicone fine particles. Among these, spherical silica particles, spherical glass beads, and spherical silicone particles are preferably used. These fine particles may be used alone or in combination of two or more.

[0020] The particle diameter of the fine particles can be designed to be smaller than the thickness of the adhesive layer (light diffusion layer), for example. If the particle diameter of the fine particles is larger than the thickness of the adhesive layer, unevenness may occur on the surface of the adhesive layer. The particle diameter of the fine particles is preferably 1 to 50 μm, more preferably 2 to 10 μm.

[0021] The content of the fine particles in the pressure-sensitive adhesive layer is, for example, 1% by weight to 50% by weight, and preferably 1% by weight to 10% by weight. In one embodiment, the haze of the pressure-sensitive adhesive layer can be controlled by adjusting the content of the fine particles in the pressure-sensitive adhesive layer.

[0022] <Polarizing film> The polarizing film is typically a film containing a dichroic material (typically, iodine). For example, the polarizing film can be formed by adsorbing and orienting iodine on a polyvinyl alcohol-based film.

[0023] The thickness of the polarizing film is not particularly limited, but is, for example, 1 μm or more and 50 μm or less. The thickness of the polarizing film is preferably 40 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. On the other hand, the thickness of the polarizing film is preferably 2 μm or more, and more preferably 3 μm or more.

[0024] The polarizing film preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The crossed transmittance (Tc) of the polarizing film is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the polarizing film is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the polarizing film is, for example, 97.0% to 99.997%, preferably 99.0% or more, more preferably 99.5% or more, and even more preferably 99.9% or more.

[0025] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0026] Examples of materials for the polyvinyl alcohol-based film include polyvinyl alcohol or its derivatives. Examples of derivatives of polyvinyl alcohol include polyvinyl formal, polyvinyl acetal, olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and those modified with alkyl esters, acrylamide, and the like. The average polymerization degree of polyvinyl alcohol is preferably 100 to 10,000, more preferably 1,000 to 10,000, and even more preferably 1,500 to 4,500. The saponification degree of polyvinyl alcohol is preferably 80 mol% to 100 mol%, and more preferably 95 mol% to 99.95 mol%. The average polymerization degree and the saponification degree can be determined in accordance with JIS K 6726.

[0027] The polyvinyl alcohol-based film may contain additives such as plasticizers and surfactants. Examples of the plasticizer include polyols such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol, and condensates thereof. The content of the additives in the polyvinyl alcohol-based film is preferably 20% by weight or less.

[0028] The iodine content (iodine concentration) of the polarizing film is, for example, 1% by weight or more and 15% by weight or less. The iodine content of the polarizing film is preferably 1.5% by weight or more, and more preferably 2% by weight or more. Within this range, the film can have excellent durability. For example, color loss can be effectively suppressed. On the other hand, the iodine content of the polarizing film is preferably 12% by weight or less, and more preferably 10% by weight or less. Within this range, for example, polyenization can be suppressed. The iodine content of the polarizing film means the amount of all iodine contained in the polarizing film. Specifically, in the polarizing film, iodine is converted into iodine ions (I - ), molecular iodine (I2), polyiodine ion (I3 - , I5 - The amount of iodine in the aqueous solution may be calculated by, for example, a calibration curve method for X-ray fluorescence analysis.

[0029] The polarizing film preferably contains a hindered amine compound. Alternatively, the polarizing film preferably contains a compound having a nitroxy radical or a nitroxide group. By containing such a compound, for example, a significant decrease in the single-unit transmittance of the polarizing film and discoloration in a high-temperature (e.g., 95°C or higher) environment can be suppressed. This is believed to be because polyenization of polyvinyl alcohol in a high-temperature environment can be suppressed. Specifically, it is believed to be because radicals generated in the polyenization reaction can be captured.

[0030] The molecular weight of the hindered amine compound is preferably not more than 1000, more preferably not more than 500, and even more preferably not more than 300. When the polarizing film contains such a compound, for example, a decrease in the single-unit transmittance of the polarizing film in a high-temperature environment can be effectively suppressed.

[0031] The molecular weight of the compound having a nitroxy radical or a nitroxide group is preferably not more than 1000, more preferably not more than 500, and even more preferably not more than 300. When the polarizing film contains such a compound, for example, a decrease in the single-unit transmittance of the polarizing film in a high-temperature environment can be effectively suppressed.

[0032] The hindered amine compound is preferably a water-soluble hindered amine compound that can dissolve, for example, 1 part by weight or more in 100 parts by weight of water at 25° C. As the hindered amine compound, a compound that can dissolve, for example, 2 parts by weight or more in 100 parts by weight of water at 25° C. is preferably used, and a compound that can dissolve, for example, 5 parts by weight or more in 100 parts by weight of water at 25° C. is more preferably used. Such a compound can be efficiently impregnated into a polarizing film, for example.

[0033] The hindered amine compound may be a secondary amine or tertiary amine in which an alkyl group is substituted on the carbon adjacent to the amino group to sterically protect the amino group, and examples of the hindered amine compound include compounds having an organic group having the structure shown below.

[0034] As the compound having the nitroxy radical or nitroxide group, an N-oxyl compound (having a functional group of CN(-C)-O) is preferred from the viewpoint of having a radical that is relatively stable in air at room temperature. · Compounds having the formula (O · The N-oxyl compound is preferably a compound having an organic group having the structure shown below.

[0035] [ka] In general formula (1), R 1 may represent an oxy radical, and R 1 may represent an oxy radical, a hydrogen atom, a hydroxy group, or an alkyl group, a hydroxyalkyl group, a hydroxyalkoxy group, or an alkoxy group having 1 to 30 carbon atoms. 2 From R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n represents 0 or 1. The left side of the dotted line in general formula (1) represents any organic group.

[0036] Examples of the compound having the organic group include compounds represented by the following general formulas (2) to (5). [ka] In general formula (2), R 1 From R 5 and n is as above, R 6 represents a hydrogen atom, or an alkyl group, acyl group, or aryl group having 1 to 10 carbon atoms. [ka] In general formula (3), R 1 From R 5 and n is as above, R 7 and R 8 each independently represents a hydrogen atom, or an alkyl group, acyl group, or aryl group having 1 to 10 carbon atoms. [ka] In general formula (4), R 1 From R 5 and n is as above, R 9 From R 11 each independently represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an acyl group, an amino group, an alkoxy group, a hydroxyl group, or an aryl group. [ka] In general formula (5), R 1 From R 5 and n is as above, R 12 represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an amino group, an alkoxy group, a hydroxyl group, or an aryl group.

[0037] In the above general formulas (1) to (5), R 1 In order to efficiently inhibit the accelerated deterioration of polyvinyl alcohol, R is preferably an oxy radical, a hydrogen atom, a hydroxy group, or an alkyl group, and more preferably an oxy radical group. 2 From R 5 is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms, from the viewpoint of availability, for example. 6 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 7 and R 8 are preferably independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 9 From R 11 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. In the above general formula (5), for example, from the viewpoint of availability, R 12 is preferably a hydroxy group, an amino group, or an alkoxy group. In the above general formulas (1) to (5), n is preferably 1, for example, from the viewpoint of availability.

[0038] The hindered amine compound may include, for example, 2,2,6,6-tetraalkylpiperidine compounds, or acid addition salts thereof or complexes thereof with metal compounds, as described in columns 5 to 11 of U.S. Pat. No. 4,619,956 and columns 3 to 5 of U.S. Pat. No. 4,839,405.

[0039] Examples of the N-oxyl compound include those described in JP 2003-64022 A, JP 11-222462 A, JP 2002-284737 A, WO 2016 / 047655, etc. Examples of the compound having the nitroxy radical or nitroxide group include the following compounds. [ka] In the general formula (6), R represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms. [ka] [ka]

[0040] The content of the hindered amine compound in the polarizing film is, for example, 0.005% by weight or more, preferably 0.01% by weight or more, and more preferably 0.02% by weight or more. With such a content, for example, the decrease in the single transmittance of the polarizing film in a high-temperature environment can be effectively suppressed. On the other hand, the content of the hindered amine compound in the polarizing film is, for example, 20% by weight or less, preferably 15% by weight or less, more preferably 12% by weight or less, and even more preferably 10% by weight or less.

[0041] The content of the compound having a nitroxy radical or a nitroxide group in the polarizing film is, for example, 0.005% by weight or more, preferably 0.01% by weight or more, and more preferably 0.02% by weight or more. With such a content, for example, the decrease in the single transmittance of the polarizing film in a high-temperature environment can be effectively suppressed. On the other hand, the content of the compound having a nitroxy radical or a nitroxide group in the polarizing film is, for example, 20% by weight or less, preferably 15% by weight or less, more preferably 12% by weight or less, and even more preferably 10% by weight or less.

[0042] The polarizing film can be produced by any suitable method. Specifically, the polarizing film can be obtained by subjecting a polyvinyl alcohol-based film (including a polyvinyl alcohol-based resin layer provided on a substrate) to various treatments such as dyeing with iodine, stretching, swelling, crosslinking, washing, and drying. Since the various treatments are well known and commonly used in the art, detailed explanations are omitted.

[0043] When at least one of the hindered amine compound and the compound having a nitroxy radical or a nitroxide group (hereinafter, sometimes simply referred to as the specified compound) is contained in the polarizing film, for example, the specified compound is contained in a treatment bath used in at least one of the various treatments. In one embodiment, the specified compound is contained in a washing bath in a washing treatment after the dyeing treatment, crosslinking treatment, and stretching treatment are performed. According to such an embodiment, the content of the specified compound and the content of iodine in the obtained polarizing film can be well adjusted.

[0044] The concentration of the predetermined compound contained in the treatment bath is, for example, 0.01% by weight to 30% by weight, preferably 0.05% by weight to 25% by weight, and more preferably 0.1% by weight to 20% by weight.

[0045] The treatment baths used in the above-mentioned various treatments (for example, dyeing, stretching, swelling, crosslinking, and washing) may contain additives. Examples of additives include zinc salts, pH adjusters, pH buffers, and other salts. Examples of zinc salts include zinc halides such as zinc chloride and zinc iodide; and inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid; and strong bases such as sodium hydroxide and potassium hydroxide. Examples of pH buffers include carboxylic acids such as acetic acid, oxalic acid, and citric acid, and salts thereof, and inorganic weak acids such as phosphoric acid and carbonic acid, and salts thereof. Examples of other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0046] <Protective layer> The protective layers may be made of any suitable film that can be used as a protective layer for a polarizing film. Examples of materials that are the main components of the films that make up the protective layers include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins. Here, (meth)acrylic refers to acrylic and / or methacrylic.

[0047] The protective layer (for example, the second protective layer 22) may be subjected to a surface treatment such as a hard coat treatment, if necessary. Specifically, the protective layer may be composed of a laminated film having the above-mentioned film as a substrate and a surface treatment layer formed on the substrate. The thickness of the surface treatment layer is preferably 1 μm to 20 μm, more preferably 3 μm to 15 μm, and further preferably 5 μm to 12 μm.

[0048] The thickness of the protective layer can be appropriately set. The thickness of the protective layer is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. Note that, when the protective layer is surface-treated, the thickness of the protective layer includes the thickness of the surface treatment layer.

[0049] In one embodiment, the protective layer (for example, the first protective layer 21) is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm. In another embodiment, the protective layer (for example, the first protective layer 21) may function as a retardation layer.

[0050] <Adhesive layer> The form of the adhesive constituting the adhesive layer is not particularly limited, and for example, a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray curing adhesive, etc. are used. Among these, for example, a water-based adhesive or an active energy ray curing adhesive is preferably used because it can reduce the thickness of the adhesive layer. The thickness of the adhesive layer is preferably 0.01 μm to 5 μm, more preferably 0.03 μm to 3 μm.

[0051] <Adhesive layer> The pressure-sensitive adhesive layers may each be set to any appropriate thickness. For example, in the first embodiment, the thicknesses of the first pressure-sensitive adhesive layer 41 and the second pressure-sensitive adhesive layer 42 are preferably 1 μm to 50 μm, more preferably 5 μm to 30 μm. The thickness of the third pressure-sensitive adhesive layer 43 is preferably 20 μm to 500 μm, more preferably 100 μm to 300 μm. For example, in the second embodiment, the thickness of the first pressure-sensitive adhesive layer 41 is preferably 1 μm to 50 μm, more preferably 5 μm to 30 μm. The thickness of the second pressure-sensitive adhesive layer 42 is preferably 20 μm to 500 μm, more preferably 100 μm to 300 μm.

[0052] The adhesive layer may be made of any suitable adhesive. As a specific example, the adhesive layer may be made of an adhesive having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like as a base polymer. By adjusting the type, number, combination, and compounding ratio of the monomers constituting the base polymer of the adhesive, as well as the compounding amount of the crosslinking agent, the reaction temperature, the reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base polymer of the adhesive may be used alone or in combination of two or more kinds. An acrylic polymer is preferably used as the base polymer. Specifically, the adhesive layer is preferably made of an acrylic adhesive.

[0053] The first pressure-sensitive adhesive layer 41 may be required to have, for example, durability (for example, prevention of coloring due to heating). The first pressure-sensitive adhesive layer 41 is formed, for example, from a pressure-sensitive adhesive composition including a (meth)acrylic polymer containing an alkyl (meth)acrylate and a crosslinking agent.

[0054] The (meth)acrylic polymer typically contains an alkyl (meth)acrylate as a main component, where (meth)acrylate refers to acrylate and / or methacrylate.

[0055] Examples of the alkyl group contained in the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. Specific examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, amyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isomyristyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl groups. These may be used alone or in combination. The average carbon number of the alkyl group is preferably 3 to 9.

[0056] The content of the alkyl (meth)acrylate in the (meth)acrylic polymer is, for example, 50 to 95 parts by weight, and preferably 70 to 90 parts by weight, based on 100 parts by weight of the monomer forming the (meth)acrylic polymer.

[0057] As the monomer component constituting the (meth)acrylic polymer, in addition to the alkyl (meth)acrylate, one or more copolymerizable monomers selected from aromatic ring-containing (meth)acrylates, amide group-containing monomers, carboxyl group-containing monomers, and hydroxyl group-containing monomers can be used. These copolymerizable monomers can be used alone or in combination.

[0058] The aromatic ring-containing (meth)acrylate is a compound that contains an aromatic ring structure in its structure and contains a (meth)acryloyl group. Examples of the aromatic ring of the aromatic ring-containing (meth)acrylate include a benzene ring, a naphthalene ring, and a biphenyl ring. Specific examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxyethyl (meth)acrylate, ethyl ethyl ester ... Examples of the acrylate include those having a benzene ring such as 3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, cresyl (meth)acrylate, and polystyryl (meth)acrylate; those having a naphthalene ring such as hydroxyethylated β-naphthol acrylate, 2-naphthoethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate; and those having a biphenyl ring such as biphenyl (meth)acrylate. Among these, for example, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferably used from the viewpoint of improving adhesive properties and durability.

[0059] When an aromatic ring-containing (meth)acrylate is used as the monomer component, the aromatic ring-containing (meth)acrylate is preferably 3% by weight or more, more preferably 8% by weight or more, and even more preferably 12% by weight or more, based on the total monomer components constituting the (meth)acrylic polymer. The upper limit of the copolymerization amount of the aromatic ring-containing (meth)acrylate is preferably 25% by weight or less, more preferably 22% by weight or less, and even more preferably 20% by weight or less.

[0060] The amide group-containing monomer is a compound that contains an amide group in its structure and also contains a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the amide group-containing monomer include acrylamide-based monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl group-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. Among these, for example, from the viewpoint of improving durability, N-vinyl group-containing lactam monomers are preferably used.

[0061] The carboxyl group-containing monomer is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Among these, for example, acrylic acid is preferably used from the viewpoint of improving adhesive properties.

[0062] The hydroxyl group-containing monomer is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; and (4-hydroxymethylcyclohexyl)-methyl acrylate. Among these, for example, from the viewpoint of improving durability, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferably used, and 4-hydroxybutyl (meth)acrylate is more preferably used.

[0063] When a hydroxyl group-containing monomer is used as the monomer component, the hydroxyl group-containing monomer is preferably 0.01% by weight or more, more preferably 0.03% by weight or more, and even more preferably 0.05% by weight or more, based on the total monomer components constituting the (meth)acrylic polymer. The upper limit of the copolymerization amount of the hydroxyl group-containing monomer is preferably 10% by weight or less, more preferably 5% by weight or less, even more preferably 2% by weight or less, and particularly preferably 1% by weight or less.

[0064] The weight average molecular weight Mw of the (meth)acrylic polymer is, for example, 100×10 4 ~300×10 4 and preferably 120×10 4 ~200×10 4The weight average molecular weight (Mw) / number average molecular weight (Mn), which indicates the molecular weight distribution, is preferably 1.8 to 10, more preferably 1.8 to 7, and further preferably 1.8 to 5. The weight average molecular weight and the molecular weight distribution (Mw / Mn) are determined from values ​​measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.

[0065] As the crosslinking agent, an isocyanate-based crosslinking agent and / or a peroxide-based crosslinking agent is preferably used, and it is more preferable to use an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent in combination.

[0066] As the isocyanate-based crosslinking agent, a compound having at least two isocyanate groups (including an isocyanate regenerating functional group in which the isocyanate group is temporarily protected by a blocking agent or oligomerization) can be used. For example, aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates that can be used in urethanization reactions can be used.

[0067] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate. Examples of the alicyclic polyisocyanate include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate. Examples of the aromatic polyisocyanate include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0068] Examples of the isocyanate-based crosslinking agent include polymers (dimers, trimers, pentamers, etc.) of the above diisocyanates, urethane-modified products reacted with polyhydric alcohols such as trimethylolpropane, urea-modified products, biuret-modified products, alphanate-modified products, isocyanurate-modified products, and carbodiimide-modified products.

[0069] Examples of commercially available isocyanate crosslinking agents include those manufactured by Tosoh Corporation under the trade names "Millionate MT," "Millionate MTL," "Millionate MR-200," "Millionate MR-400," "Coronate L," "Coronate HL," "Coronate HX," and "Coronate 2770," and those manufactured by Mitsui Chemicals, Inc. under the trade names "Takenate D-110N," "Takenate D-120N," "Takenate D-140N," "Takenate D-160N," "Takenate D-165N," "Takenate D-170HN," "Takenate D-178N," "Takenate 500," and "Takenate 600."

[0070] In one embodiment, aromatic polyisocyanates and their modified aromatic polyisocyanates, and aliphatic polyisocyanates and their modified aliphatic polyisocyanates are preferably used as the isocyanate crosslinking agent. Aromatic polyisocyanate compounds are preferably used because they have a good balance between crosslinking speed and pot life. Tolylene diisocyanate and its modified aromatic polyisocyanates are particularly preferably used as the aromatic polyisocyanate compounds. In another embodiment, non-aromatic ring-based compounds are preferably used as the isocyanate crosslinking agent. In this specification, "non-aromatic ring-based" means a compound that does not contain an aromatic ring. Examples of non-aromatic ring-based isocyanate crosslinking agents are alicyclic isocyanate compounds, aliphatic isocyanate compounds, and derivatives thereof. The non-aromatic ring-based isocyanate crosslinking agent may be an aliphatic isocyanate compound and its derivative, or a hexamethylene diisocyanate (HDI) compound and its derivative.

[0071] The peroxide-based crosslinking agent is not particularly limited as long as it generates radical active species by heating or light irradiation to promote crosslinking of the (meth)acrylic polymer. For example, from the viewpoint of workability and stability, it is preferable to use a peroxide-based crosslinking agent having a 1-minute half-life temperature of 80°C to 160°C, and it is more preferable to use a peroxide-based crosslinking agent having a 1-minute half-life temperature of 90°C to 140°C.

[0072] The amount of the crosslinking agent is preferably 0.01 to 3 parts by weight, more preferably 0.02 to 2 parts by weight, and even more preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer. When an isocyanate-based crosslinking agent is used as the crosslinking agent, the amount is preferably 0.01 to 2 parts by weight, more preferably 0.02 to 1.5 parts by weight, and even more preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer, and may be less than 1 part by weight, 0.8 parts by weight or less, or 0.6 parts by weight or less. When a peroxide-based crosslinking agent is used as the crosslinking agent, the amount is preferably 0.01 to 2 parts by weight, more preferably 0.04 to 1.5 parts by weight, and even more preferably 0.05 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer.

[0073] The pressure-sensitive adhesive composition may contain a silicon compound, which is preferably one or more compounds selected from alkoxysilane compounds and organopolysiloxane compounds, each of which has an acidic group or an acid anhydride group derived from an acidic group in the molecule and does not have a polyether group, and / or a hydrolysis condensate thereof.

[0074] The acidic group is preferably a carboxyl group. The acidic group may be a group generated by hydrolysis of an acid anhydride group. Specific examples of the acid anhydride group include carboxylic anhydride groups such as succinic anhydride group, phthalic anhydride group, and maleic anhydride group, and the succinic anhydride group is preferred.

[0075] The above-mentioned specific alkoxysilane compound is, for example, a compound represented by the general formula (I): R 1 R 2 a Si(OR 3 ) 3-a It is expressed as: In general formula (I), R 1is an organic group having 1 to 20 carbon atoms and having an acidic group or an acid anhydride group. This organic group may be linear, branched, or cyclic. In general formula (I), R 2 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a hydrogen atom or a halogen atom. 3 each independently represents an alkyl group having 1 to 10 carbon atoms, and a is an integer of 0 or 1.

[0076] In the above general formula (I), R 1 From the viewpoint of availability, is preferably an organic group represented by the following general formula (II). [ka] In general formula (II), A represents a linear or branched alkylene or alkenylene group having 2 to 10 carbon atoms, and preferably represents a linear or branched alkylene group having 2 to 6 carbon atoms.

[0077] Examples of the above-mentioned specified alkoxysilane compound include 2-trimethoxysilylethylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., product name "X-12-967C"), 3-trimethoxysilylpropylsuccinic anhydride, 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.

[0078] The above-mentioned specific organopolysiloxane compound is a compound having a siloxane bond, and contains, for example, a siloxane unit (U1) represented by the following formula (III). The above-mentioned specific organopolysiloxane compound may further contain a siloxane unit (U2) represented by the following formula (IV). [ka] [ka]

[0079] In formula (III), X is an organic group having an acidic group or an acid anhydride group, and is preferably an organic group represented by formula (II). 4 R are each independently a hydrogen atom, an alkoxy group having 1 to 10 carbon atoms, or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 4 The alkoxy group in R is preferably a methoxy group or an ethoxy group. 4 The hydrocarbon group is, for example, a methyl group.

[0080] The number of siloxane units (U1) contained in the organopolysiloxane compound is not particularly limited and is, for example, 1 to 100, preferably 1 to 50, and more preferably 1 to 20. The number of siloxane units (U2) contained in the organopolysiloxane compound is not particularly limited and is, for example, 0 to 100, preferably 0 to 50, and more preferably 0 to 20. The organopolysiloxane compound preferably contains at least one siloxane unit (U2).

[0081] The organopolysiloxane compound may have a structure in which at least one siloxane unit (U1) is inserted between the O-Si bonds contained in an alkoxysilane represented by the following formula (V) or a partial hydrolysis condensate thereof. Both the siloxane unit (U1) and the siloxane unit (U2) may be inserted between the O-Si bonds. Of the multiple O-Si bonds, the siloxane unit (U1) may be inserted between some of the O-Si bonds, and the siloxane unit (U2) may be inserted between the other O-Si bonds. R 5 n Si(OR 6 ) 4-n (V)

[0082] In formula (V), R 5 are each independently a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a hydrogen atom or a halogen atom.6 are each independently an alkyl group having 1 to 10 carbon atoms. In formula (V), n is 0 or 1.

[0083] Examples of the alkoxysilane represented by formula (V) or its partial hydrolysis condensation product include tetramethoxysilane, methyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, and compounds obtained by partial hydrolysis condensation of one or more of these alkoxysilanes.

[0084] The above-mentioned specific organopolysiloxane compound can be produced by a known production method described in, for example, JP-A-2013-129809, JP-A-2013-129691, and the like.

[0085] The amount of the silicon compound is preferably 0.1 parts by weight or more and 3.0 parts by weight or less, more preferably 0.2 parts by weight or more and 2.0 parts by weight or less, even more preferably 0.2 parts by weight or more and 1.0 parts by weight or less, and particularly preferably 0.4 parts by weight or more and 0.6 parts by weight or less, based on 100 parts by weight of the (meth)acrylic polymer.

[0086] The pressure-sensitive adhesive composition may contain a reactive functional group-containing silane coupling agent. The reactive functional group of the reactive functional group-containing silane coupling agent may be a functional group other than an acid anhydride group. The functional group other than an acid anhydride group is preferably one or more functional groups selected from an epoxy group, a mercapto group, an amino group, an isocyanate group, an isocyanurate group, a vinyl group, a styryl group, an acetoacetyl group, a ureido group, a thiourea group, a (meth)acrylic group, and a heterocyclic group.

[0087] Examples of the reactive functional group-containing silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and 3-triethoxy Examples of the silane coupling agents include amino group-containing silane coupling agents such as silyl-N-(1,3-dimethylbutylidene)propylamine and N-phenyl-γ-aminopropyltrimethoxysilane; isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane; vinyl group-containing silane coupling agents such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing silane coupling agents such as p-styryltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane. Among these, epoxy group-containing silane coupling agents and mercapto group-containing silane coupling agents are preferred.

[0088] As the reactive functional group-containing silane coupling agent, an oligomer type silane coupling agent having a plurality of alkoxysilyl groups in the molecule can also be used. Specific examples include epoxy group-containing oligomer type silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., trade names "X-41-1053", "X-41-1059A", "X-41-1056", and "X-40-2651"; and mercapto group-containing oligomer type silane coupling agents "X-41-1818", "X-41-1810", and "X-41-1805". The oligomer type silane coupling agent is difficult to volatilize, and has a plurality of alkoxysilyl groups, so it can be effective in improving durability.

[0089] When the pressure-sensitive adhesive composition is blended with a reactive functional group-containing silane coupling agent, the blending amount of the reactive functional group-containing silane coupling agent is preferably 0.001 to 5 parts by weight, more preferably 0.01 to 1 part by weight, and even more preferably 0.05 to 0.6 parts by weight, relative to 100 parts by weight of the (meth)acrylic polymer. In addition, the weight ratio of the silicon compound and the reactive functional group-containing silane coupling agent (blended amount of silicon compound / blended amount of reactive functional group-containing silane coupling agent) is, for example, preferably 0.1 to 50, more preferably 0.5 to 15, and even more preferably 1 to 5, from the viewpoint of improving durability.

[0090] The pressure-sensitive adhesive composition may contain a conductive agent. Any appropriate conductive agent may be used as the conductive agent. An organic cationic conductive agent is preferably used as the conductive agent. The organic cationic conductive agent may typically be an organic cationic salt. The cationic portion (cation component) of the organic cationic salt may have an organic structure. The anionic portion (anionic component) of the organic cationic salt may have an organic structure or an inorganic structure. The organic cationic salt may be an ionic solid having a melting point of 40° C. or higher.

[0091] An example of the cation is an organic onium containing an organic group. An example of the onium contained in the organic onium is a nitrogen-containing onium, a sulfur-containing onium, or a phosphorus-containing onium, and preferably a nitrogen-containing onium or a sulfur-containing onium. An example of the nitrogen-containing onium is an ammonium cation, a piperidinium cation, a pyrrolidinium cation, a pyridinium cation, a cation having a pyrroline skeleton, a cation having a pyrrole skeleton, an imidazolium cation, a tetrahydropyrimidinium cation, a dihydropyrimidinium cation, a pyrazolium cation, or a pyrazolinium cation. An example of the sulfur-containing onium is a sulfonium cation. An example of the phosphorus-containing onium is a phosphonium cation. An example of the organic group contained in the organic onium is an alkyl group, an alkoxyl group, or an alkenyl group. A specific example of a preferred organic onium is a tetraalkylammonium cation (e.g., a tributylmethylammonium cation), an alkylpiperidinium cation, or an alkylpyrrolidinium cation.

[0092] An example of the above anion is Cl. - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , C4F9SO3 - , C3F7COO - , (CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - and anions represented by the following general formulas (a) to (d). (a)(Cn F 2n+1 SO2)2N - (n is an integer between 1 and 10) (b) CF2(C m F 2m SO2)2N - (m is an integer between 1 and 10) (c) - O3S(CF2) l SO3 - (l is an integer between 1 and 10) (d)(C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (p and q are each independently an integer from 1 to 10).

[0093] Specific examples of organic cationic conductive agents are 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) and trimethylbutylammonium bis(trifluoromethanesulfonyl)imide.

[0094] The amount of the organic cationic conductive agent to be blended is, for example, 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.7 parts by weight or more, 0.9 parts by weight or more, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, or even 7 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic polymer. The upper limit of the blending amount is, for example, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or even 1.5 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer.

[0095] <Support> The support is provided adjacent to, for example, a pressure-sensitive adhesive layer that can function as a light diffusion layer. A support having appropriate mechanical strength is used as the support. For example, a film (laminated film) on which the hard coat layer is formed is used as such a support. The thickness of the hard coat layer is preferably 1 μm to 20 μm, more preferably 3 μm to 15 μm, and even more preferably 5 μm to 12 μm. Examples of materials that are the main components of the film constituting the support include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic-based, acetate-based, and other resins. The thickness of the support (film on which the hard coat layer is formed) is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and even more preferably 20 μm to 50 μm.

[0096] [Display device] The optical laminate can be used in a display device, and a display device according to an embodiment of the present invention includes the optical laminate. Fig. 3 is a schematic cross-sectional view showing an outline of a liquid crystal display device according to one embodiment of the present invention. Specifically, it is a schematic cross-sectional view showing a display panel unit included in a liquid crystal display device according to one embodiment of the present invention.

[0097] The panel unit 1 of the liquid crystal display device includes a first display panel 100, a second display panel 200 disposed closer to a viewer than the first display panel 100, an optical laminate 60 disposed between the first display panel 100 and the second display panel 200, and a backlight 300 that irradiates the multiple display panels with light from the rear side. The optical laminate 60 is attached to the first display panel 100 by a first adhesive layer 41, and is attached to the second display panel 200 by a third adhesive layer 43. In Fig. 3, the upper side is the viewer side, and although not shown, a transparent plate may be provided on the viewer side of the first display panel 100.

[0098] The first display panel 100 includes a first liquid crystal cell 101 and a first polarizing plate 102 arranged on the backlight 300 side of the first liquid crystal cell 101. The second display panel 200 includes a second liquid crystal cell 201 and a second polarizing plate 202 arranged on the viewer side of the second liquid crystal cell 201. The first liquid crystal cell 101 and the second liquid crystal cell 201 each include a thin film transistor substrate (TFT substrate), a color filter substrate (CF substrate), and a liquid crystal layer arranged between the TFT substrate and the CF substrate, which are not shown. Any appropriate driving method may be adopted as a driving method for the first liquid crystal cell 101 and the second liquid crystal cell 201.

[0099] As described above, since the optical laminate 60 can include a light diffusion layer, the occurrence of moire can be suppressed in the liquid crystal display device of this embodiment. For example, the occurrence of moire caused by the pattern of the black matrix of the CF substrate between the first liquid crystal cell 101 and the second liquid crystal cell 201 can be suppressed.

[0100] For example, when the polarizing plate 30 is exposed to a high temperature environment while moisture is present in the polarizing plate 30, the acid present in the adhesive layer may migrate to the polarizing film 10 and act as an acid catalyst for polyenation by dehydration of polyvinyl alcohol in the polarizing film 10. In a configuration in which the display panels 100 and 200 are arranged on both sides of the polarizing plate 30, it is considered that the moisture in the polarizing plate 30 is less likely to escape and polyenation is more likely to be promoted. Thus, even in an environment in which polyenation is easily promoted, the presence of a specific compound in the polarizing film 10 can suppress polyenation. As a result, it is considered that the decrease in the single transmittance of the polarizing film 10 can be suppressed. The effect of the acid present in the adhesive layer may be greater as the adhesive layer becomes thicker.

[0101] In the optical laminate 60, the first pressure-sensitive adhesive layer 41 attached to the first display panel 100 arranged on the backlight 300 side is susceptible to the heat and / or light of the backlight 300. In a configuration in which the display panels 100, 200 are arranged on both sides of the optical laminate 60, radicals are likely to be generated at the end including the end face of the first pressure-sensitive adhesive layer 41 in contact with air (oxygen), and for example, yellowing may occur. By forming the first pressure-sensitive adhesive layer 41, which is susceptible to the heat and / or light of the backlight 300, from the pressure-sensitive adhesive composition, for example, the occurrence of the above-mentioned yellowing can be suppressed.

[0102] In one embodiment, the first adhesive layer 41, which is susceptible to the influence of the backlight 300, is substantially free of fine particles. In this embodiment, the first adhesive layer 41 can have excellent adhesive properties to the first display panel 100.

[0103] Since the optical laminate 60 includes a pressure-sensitive adhesive layer with a high haze (for example, a haze of 66% or more), the light amount of the backlight 300 may be increased in order to ensure brightness. In this case, the polarizing plate 30 and / or the first pressure-sensitive adhesive layer 41 are further affected by the heat and / or light of the backlight 300, and the above-mentioned problems of polyenation and / or yellowing are likely to occur. EXAMPLES

[0104] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The thickness, haze, iodine concentration, and weight average molecular weight (Mw) are values ​​measured by the following measurement methods. Furthermore, unless otherwise specified, "parts" and "%" are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Haze> The haze was measured according to JIS K 7136 using a haze meter (manufactured by Murakami Color Science Laboratory, product name "HN-150"). <Iodine concentration> The polarizing film was measured using a fluorescent X-ray analyzer (Rigaku Corporation, "ZSX-PRIMUS IV") with a measurement diameter of φ20 mm, and the iodine concentration (wt%) was calculated using the following formula. Note that the following coefficients for calculating the iodine concentration differ depending on the measurement device, for example, but can be calculated using an appropriate calibration curve. Iodine concentration (wt%) = 14.474 × (fluorescent X-ray intensity) / (film thickness) (kcps / μm) <Weight average molecular weight (Mw)> The weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC). Mw / Mn was also measured in the same manner. Analytical equipment: Tosoh HLC-8120GPC Column: Tosoh G7000H XL +GMH XL +GMH XL Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8mL / min ·Injection volume: 100μL Eluent: Tetrahydrofuran Detector: Differential refractometer (RI) Standard sample: polystyrene

[0105] [Example 1] (Preparation of Polarizing Film 1) A polyvinyl alcohol film having an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol %, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was stretched to 2.2 times its original size in the conveying direction while being swollen by being immersed in a swelling bath (water bath) at 20°C for 30 seconds between rolls with different peripheral speed ratios (swelling step), and then, while being dyed by being immersed in a dyeing bath at 30°C (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) for 30 seconds while adjusting the iodine concentration in the finally obtained polarizing film to 4.47% by weight, the film was stretched to 3.3 times its original size in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film that was not stretched at all in the conveying direction) (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a 40°C crosslinking bath (an aqueous solution containing 3.0% by weight of boric acid and 3.0% by weight of potassium iodide) for 28 seconds and stretched to 3.6 times the original size of the polyvinyl alcohol film in the conveying direction (crosslinking step). The obtained polyvinyl alcohol film was then immersed in a 61°C stretching bath (aqueous solution with a boric acid concentration of 4.0% by weight and a potassium iodide concentration of 5.0% by weight) for 60 seconds to stretch the film to 6.0 times the original polyvinyl alcohol film in the conveying direction (stretching step), and then immersed in a 35°C washing bath (aqueous solution with a potassium iodide concentration of 2.0% by weight and a compound represented by the following general formula (9) concentration of 0.4% by weight) for 10 seconds (washing step). The washed polyvinyl alcohol film was dried at 40°C for 30 seconds to prepare a polarizing film with a thickness of 18 μm and an iodine concentration of 4.47% by weight. The compound represented by the following general formula (9) is a compound that dissolves in 100 parts by weight of water at 25°C at a concentration of 1 part by weight or more. Approximately 20 mg of the obtained polarizing film was sampled, quantified, and dissolved by heating in 1 mL of water, and then diluted with 4.5 mL of methanol. The obtained extract was filtered through a membrane filter, and the content of the compound represented by the following general formula (9) in the polarizing film was measured using HPLC (Waters, "ACQUITY UPLC H-class Bio"), which was 0.28% by weight. [ka]

[0106] (Preparation of polarizing plate) A 30 μm-thick acrylic film made of an acrylic polymer having a lactone ring structure was attached to one surface (first main surface) of the polarizing film using a polyvinyl alcohol adhesive. Next, a 49 μm-thick HC-TAC film was attached to the other surface (second main surface) of the polarizing film using a polyvinyl alcohol adhesive. The 49 μm-thick HC-TAC film was a laminated film in which a 9 μm-thick hard coat (HC) layer was formed on a 40 μm-thick triacetyl cellulose (TAC) film (Konica Minolta, Inc., "KC4UY"), and the laminated film was attached so that the TAC film faced the polarizing film side to obtain a laminate. The resulting laminate was heated and dried in an oven set at 70° C. for 5 minutes to prepare a polarizing plate.

[0107] (Preparation of Acrylic Pressure Sensitive Adhesive Composition 1) A monomer mixture containing 76.9 parts by weight of butyl acrylate, 18 parts by weight of benzyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate for 100 parts by weight of this monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 55°C and a polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.95 million and Mw / Mn=3.9. Acrylic adhesive composition 1 was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 0.4 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, Tosoh Corporation, "Coronate L"), 0.1 parts by weight of a peroxide crosslinking agent (NOF Corporation, "Niper BMT"), 0.2 parts by weight of a silane coupling agent (Shin-Etsu Chemical Co., Ltd., "X-41-1056"), and 0.6 parts by weight of the following organopolysiloxane compound.

[0108] (Preparation of organopolysiloxane compounds) An organopolysiloxane compound was prepared according to the method described in Example 1 of JP 2013-129809 A. This organopolysiloxane compound contained the above-mentioned siloxane units (U1) and (U2). In the siloxane unit (U1), X is a propylsuccinic anhydride group, R 4 was a methyl group. In the siloxane unit (U2), two R 4 In both cases, the siloxane units (U1) and (U2) in the organopolysiloxane compound were 27 mol % and 73 mol %, respectively. The weight average molecular weight of the compound was about 1,000.

[0109] (Formation of first adhesive layer) The above acrylic adhesive composition 1 was applied to a release liner (polyethylene terephthalate film treated with a silicone-based release agent, thickness 38 μm, manufactured by Mitsubishi Chemical Polyester Film Corporation, "MRF38") so that the adhesive layer would have a thickness of 20 μm after drying, and was dried at 155° C. for 1 minute to form a first adhesive layer on the release liner.

[0110] (Preparation of polarizing plate with adhesive layer) The first pressure-sensitive adhesive layer was attached to the acrylic film side of the polarizing plate to obtain a pressure-sensitive adhesive layer-attached polarizing plate.

[0111] (Preparation of light diffusion layer forming composition) 100 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of hydroxyethyl acrylate were solution polymerized to obtain an acrylic polymer having a weight average molecular weight (Mw) of 2,000,000. 100 parts by weight of the obtained acrylic polymer, 0.6 parts by weight of an isocyanate-based crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, Tosoh Corporation, "Coronate L"), 0.1 parts by weight of a silane coupling agent (Shin-Etsu Silicones, "KBM403"), and 7 parts by weight of spherical microparticles (silicone resin with refractive index: 1.42, average particle size: 4.5 μm, Momentive Performance Materials Japan, Inc., "Tospearl 145") were added to toluene to give a solid content of 10% by weight, and the mixture was stirred in a Dispaster for 15 minutes to disperse the microparticles, thereby preparing a light diffusion layer-forming composition.

[0112] (Formation of second adhesive layer) The obtained light diffusion layer forming composition was applied to the polarizing plate side surface of the above-mentioned adhesive layer-attached polarizing plate using a wire bar so that the dried thickness was 23 μm, and then dried to form a second adhesive layer with a haze of 85%.

[0113] (Preparation of optical laminate) Next, a 49 μm-thick HC-TAC film was attached to the second adhesive layer of the adhesive layer-attached polarizing plate, and a 250 μm-thick adhesive layer was further formed on the surface of the HC-TAC film to produce an optical laminate.

[0114] [Example 2] An optical laminate was produced in the same manner as in Example 1, except that in the preparation of the light diffusion layer-forming composition, the amount of spherical fine particles was 5 parts by weight, and a second pressure-sensitive adhesive layer with a haze of 80% was formed.

[0115] [Example 3] An optical laminate was produced in the same manner as in Example 1, except that in the preparation of the light diffusion layer-forming composition, the amount of spherical fine particles was 4 parts by weight, and a second pressure-sensitive adhesive layer with a haze of 75% was formed.

[0116] [Example 4] An optical laminate was produced in the same manner as in Example 1, except that the first pressure-sensitive adhesive layer was formed using acrylic pressure-sensitive adhesive composition 2 described below.

[0117] (Preparation of Acrylic Pressure Sensitive Adhesive Composition 2) A monomer mixture containing 77.95 parts by weight of butyl acrylate, 16 parts by weight of phenoxyethyl acrylate, 3 parts by weight of acrylic acid, 1 part by weight of N-vinyl-2-pyrrolidone, and 0.05 parts by weight of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 55°C and a polymerization reaction was carried out for 6 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.5 million and Mw / Mn=3.0. Acrylic adhesive composition 2 was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 0.5 parts by weight of a non-aromatic isocyanate crosslinking agent (an allophanate obtained by addition reaction of hexamethylene diisocyanate with acrylic polyol, manufactured by Tosoh Corporation, "Coronate 2770"), 0.2 parts by weight of a peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, "Niper BMT"), and 1 part by weight of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI).

[0118] [Example 5] An optical laminate was produced in the same manner as in Example 2, except that the first pressure-sensitive adhesive layer was formed using the acrylic pressure-sensitive adhesive composition 2 described above.

[0119] [Example 6] An optical laminate was produced in the same manner as in Example 3, except that the first pressure-sensitive adhesive layer was formed using the acrylic pressure-sensitive adhesive composition 2 described above.

[0120] [Example 7] An optical laminate was produced in the same manner as in Example 2, except that the first pressure-sensitive adhesive layer was formed using acrylic pressure-sensitive adhesive composition 3 described below.

[0121] (Preparation of Acrylic Pressure-Sensitive Adhesive Composition 3) A monomer mixture containing 77.95 parts by weight of butyl acrylate, 16 parts by weight of phenoxyethyl acrylate, 3 parts by weight of acrylic acid, 1 part by weight of N-vinyl-2-pyrrolidone, and 0.05 parts by weight of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 55°C and a polymerization reaction was carried out for 6 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.5 million and Mw / Mn=3.0. Acrylic adhesive composition 3 was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 1 part by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, Tosoh Corporation, "Coronate L"), 0.2 parts by weight of a peroxide crosslinking agent (NOF Corporation, "Niper BMT"), 0.5 parts by weight of lithium bis(trifluoromethanesulfonyl)imide, 0.05 parts by weight of a silane coupling agent (Shin-Etsu Chemical Co., Ltd., "X-41-1056"), 0.4 parts by weight of a polyether compound (Kaneka Corporation, "Silyl SAT10"), and 0.4 parts by weight of the above organopolysiloxane compound.

[0122] [Comparative Example 1] An optical laminate was produced in the same manner as in Example 1, except that in the preparation of the light diffusion layer-forming composition, the amount of spherical fine particles was 2 parts by weight, and a second pressure-sensitive adhesive layer with a haze of 55% was formed.

[0123] [Comparative Example 2] An optical laminate was produced in the same manner as in Example 2, except that a polarizing plate was produced using polarizing film 2 described below.

[0124] (Preparation of polarizing film 2) A polyvinyl alcohol film having an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol %, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was immersed in a swelling bath (water bath) at 28°C for 30 seconds between rolls with different peripheral speed ratios, where it was stretched 2.4 times in the conveying direction while swelling (swelling step), and then immersed in a dyeing bath (aqueous solution with an iodine concentration of 0.03 wt% and a potassium iodide concentration of 0.3 wt%) at 25°C for 45 seconds, where it was dyed and stretched 3.7 times in the conveying direction based on the original polyvinyl alcohol film (a polyvinyl alcohol film that was not stretched at all in the conveying direction) (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a crosslinking bath (an aqueous solution containing boric acid at a concentration of 3.0% by weight, potassium iodide at a concentration of 3.0% by weight, and zinc sulfate at a concentration of 3.6% by weight (zinc ion concentration of 1.5% by weight)) at 40°C for 20 seconds, and stretched to 4.2 times the original size of the polyvinyl alcohol film in the conveying direction (crosslinking step). Furthermore, the obtained polyvinyl alcohol film was immersed in a 65°C stretching bath (an aqueous solution having a boric acid concentration of 4.0% by weight, a potassium iodide concentration of 5.0% by weight, and a zinc sulfate concentration of 5.0% by weight (zinc ion concentration of 2.0% by weight)) for 50 seconds to be stretched to 6.0 times the original polyvinyl alcohol film in the conveying direction (stretching process), and then immersed in a 27°C washing bath (an aqueous solution having a potassium iodide concentration of 2.5% by weight) for 5 seconds (washing process). The washed polyvinyl alcohol film was dried at 25° C. for 2 minutes to prepare a polarizing film with a thickness of 18 μm.

[0125] [Comparative Example 3] An optical laminate was produced in the same manner as in Example 5, except that a polarizing plate was produced using polarizing film 2.

[0126] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Table 1. <Evaluation> 1. Moire An in-plane switching (IPS) panel (first liquid crystal display panel, second liquid crystal display panel) and a backlight for vehicle mounting were prepared. Then, as shown in Fig. 3, a first adhesive layer of the obtained optical laminate was attached to the liquid crystal cell of the first liquid crystal display panel, and a 250 μm-thick adhesive layer of the optical laminate was attached to the liquid crystal cell of the second liquid crystal display panel. Then, the backlight was turned on from the first liquid crystal display panel side, and the presence or absence of the moire phenomenon (occurrence of rainbow unevenness) was visually confirmed from the second liquid crystal display panel side. (Evaluation Criteria) Good: No moire (rainbow unevenness) can be seen Poor: Moire (rainbow unevenness) is observed. 2. Appearance 1 A 0.7 mm-thick non-alkali glass plate 1 was bonded to the 250 μm-thick adhesive layer of the optical laminate. Thereafter, the release liner used to form the first adhesive layer was peeled off from the first adhesive layer, and a 0.7 mm-thick non-alkali glass plate 2 was bonded to the released surface to obtain an evaluation sample. The evaluation sample was left in an environment at a temperature of 95° C. for 1000 hours, and the appearance of the optical laminate after heating was visually observed under fluorescent light irradiation. (Evaluation Criteria) Good: No significant change was observed in the appearance of the optical laminate compared to a separately prepared evaluation sample (not placed in a 95°C environment). Defective: A significant color change (discoloration to brown or black) was observed in the appearance of the optical laminate compared to a separately prepared evaluation sample (not placed in an environment at a temperature of 95°C). 3. Appearance 2 The above evaluation sample was left in a heated atmosphere at a temperature of 95° C. for 500 hours. After leaving, the evaluation sample was irradiated with light from the glass plate 2 side of the evaluation sample, and the appearance of the optical laminate after irradiation was visually observed. For the evaluation, a backlight having a light-emitting area capable of irradiating light equivalent to CIE standard light source D65 with a luminous intensity of 15,000 candela was used. (Evaluation Criteria) Good: No change in appearance of the optical laminate was observed Poor: There is no change in the appearance of the optical laminate, but the edges, including the edge faces of the adhesive layer, are discolored (yellowing).

[0127] [Table 1]

[0128] Discoloration was observed in the center of the display panel in Comparative Examples 2 and 3. In Example 7, yellowing was observed at the edge of the first pressure-sensitive adhesive layer.

[0129] In Reference Examples 1 and 2 in Table 1, evaluation samples were prepared in the same manner as above, except that the alkali-free glass plate 1 was not bonded to the optical laminates of Comparative Examples 2 and 3, respectively, and were subjected to the above evaluation. In Reference Example 3 in Table 1, an evaluation sample was prepared in the same manner as above, except that the alkali-free glass plate 1 was not bonded to the optical laminate of Example 7, and was subjected to the above evaluation.

[0130] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same effect, or a configuration that can achieve the same purpose. [Industrial Applicability]

[0131] The optical laminate according to the embodiment of the present invention is preferably used in, for example, a display device configured by stacking a plurality of display panels. [Explanation of symbols]

[0132] 1. Display panel 10 Polarizing film 21 First protective layer 22 Second protective layer 30 Polarizing plate 41 First adhesive layer 42 Second adhesive layer 43 Third adhesive layer 50 Support 60 Optical laminate 61 Optical laminate 100 First display panel 200 Second display panel

Claims

1. a polarizing plate including a polarizing film having a first main surface and a second main surface facing each other; a first pressure-sensitive adhesive layer disposed on the first main surface side of the polarizing film; a second pressure-sensitive adhesive layer disposed on the second main surface side of the polarizing film, At least one of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer has a haze of 66% or more; The polarizing film is composed of a polyvinyl alcohol-based film containing iodine, and contains a compound having a nitroxy radical or a nitroxide group. Optical laminate.

2. The optical laminate according to claim 1 , wherein the second pressure-sensitive adhesive layer has a haze of 66% or more.

3. The optical laminate according to claim 2 , further comprising a third pressure-sensitive adhesive layer disposed on the second main surface side of the polarizing film.

4. The optical laminate according to claim 2 , further comprising a support disposed on the second main surface side of the polarizing film.

5. 2. The optical laminate according to claim 1, wherein the content of the compound having a nitroxy radical or a nitroxide group in the polarizing film is 20% by weight or less.

6. The optical laminate according to claim 1 , wherein the iodine content of the polarizing film is from 1% by weight to 15% by weight.

7. the first pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition including a (meth)acrylic polymer and a crosslinking agent, The crosslinking agent includes an isocyanate-based crosslinking agent, The content of the isocyanate-based crosslinking agent is less than 1 part by weight based on 100 parts by weight of the (meth)acrylic polymer. The optical laminate according to claim 1 .

8. The optical laminate according to claim 7 , wherein the isocyanate-based crosslinking agent is a non-aromatic ring system.

9. A display device in which a plurality of display panels, each including a liquid crystal cell, are arranged in a stacked manner and an image is displayed on each of the display panels, A first display panel; a second display panel disposed closer to a viewer than the first display panel; and the optical laminate according to claim 1 , which is disposed between the first display panel and the second display panel; The first pressure-sensitive adhesive layer of the optical laminate is bonded to the first display panel. Display device.

Citation Information

Patent Citations

  • Liquid crystal display device and television receiver

    JP2007310161A